Unusual presentation in Axenfeld-Rieger syndrome - Rajul S Parikh; Shefali R Parikh; B Debashish; B L Harsha; Ravi Thomas (Indian Journal of Ophthalmology, 2011)
We report an unusual presentation of a case of Axenfeld-Rieger (A-R) syndrome. A 14-year-old male presented with gradual dimness of vision for 1 year and redness of left eye for 3 days. The patient had megalocornea with Haab′s striae in the right eye and posterior embryotoxon in both the eyes. In the left eye, there was a white cord-like structure traversing the anterior chamber with adhesions to iris tissue along its course. On two antiglaucoma medications, his intraocular pressure (IOP) was 22 mm Hg in the right eye and 18 mm Hg in the left eye. Gonioscopy revealed a cord-like structure originating at the level of Schwalbe′s line. He underwent right eye trabeculectomy with mitomycin-C. This case highlights a rare presentation of a strange cord-like structure, a rare presentation of A-R syndrome.